Les premières institutions municipales au Québec ou « machines à taxer » - L’Heureux, Jacques (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1979)
The first general municipal institutions in Quebec were adopted by the Special Council in 1840 when Governor Sydenham found that the Act of Union did not make provision for them. These institutions included local corporations — parishes and townships — and regional corporations — the districts. Parishes and townships had very few powers. Districts had limited powers on local matters. All municipal corporations had little autonomy and were under the strict control of the Governor. Nevertheless, their creation was bound to lead to more important and more autonomous municipal institutions. French Canadians were opposed to these institutions, partly because they seemed to belong to the set of post-Rebellion measures such as the union of the two Canadas and the setting up of the Special Council, and partly because the new municipal corporations had the power to levy taxes. Their opposition succeeded in paralysing these institutions, which were replaced by new ones in 1845.